Aspek Hukum Transaksi Jual Beli Rumah Susun/Apartemen di Daerah Istimewa Yogyakarta Kaitannya dengan Peran Notaris-PPAT - Pandam Nurwulan (Jurnal Hukum IUS QUIA IUSTUM, 2015)
This research discusses, first, whether there has been any regulatory compliance related to purchase and sale transactions of Flats/Apartments in Special Region of Yogyakarta? Second, how is the role of Land Title Registrar in such legal relationship? This was a normative legal research whose data analysis was descriptive qualitative. The conclusions are: first, there has not been any Local Regulation regarding Flats/Apartments until the present time so that Regent/Mayor Regulations (Mayor Regulation Number 7 of 2015 regarding the Certificate of Proper Function of Flat, Mayor Regulation Number 8 of 2015 regarding the Legalization of Title of Flat Separation, Mayor Regulation Number 9 of 2015 regarding the Union of Owners and Occupants of Flats and Regent Regulation of Sleman Number 40 of 2015 regarding the Legalization of Report and Title of Flat Separation are still in the form of a guideline which should have become an implementation regulation from the Local Regulation regarding purchase and sale transactions of Flats/Apartments. Second, Land Title Registrars should play their roles professionally by mastering all regulations related to Flats/Apartments so that any land titles they issue related to purchase and sale transactions of Flats/Apartments will have authenticity as a proof.